(untitled) (Acta Scientiarum. Technology, 2012)
In this paper we have introduced the notion of fuzzy real-valued p-bounded variation double sequence space 2bvp/F(1 â‰¤ p < âˆž). We have studied some important properties like completeness, convergence free, solid, symmetric. Some inclusion results are also established. Â